Antitumor Effect of Bevacizumab in a Xenograft Model of Canine Hemangiopericytoma - Masaki Michishita; Tatsuya Uto; Ryota Nakazawa; Hisashi Yoshimura; Kikumi Ogihara; Yuko Naya; Tsuyoshi Tajima; Daigo Azakami; Seigo Kishikawa; Toshiro Arai; Kimimasa Takahashi (Elsevier, 2013)
Abstract.: Canine hemangiopericytoma (CHP) is characterized by frequent local recurrence and increased invasiveness. Vascular endothelial growth factor (VEGF) is a key regulator of angiogenesis in tumors. The aim of the present study was to investigate the effect of a single dose of bevacizumab on a xenograft model of CHP. VEGF protein was secreted from cultured CHP cells and interacted with bevacizumab. Bevacizumab treatment suppressed tumor growth by inhibiting tumor angiogenesis, whereas no significant differences were observed in the proliferation index and apoptosis rates of treated and untreated mice. Thus, bevacizumab had antitumor effects in a xenograft model of CHP. Keywords:: bevacizumab, canine hemangiopericytoma, vascular endothelial growth factor (VEGF)